Heterogeneity and Spatial Governance of Synergy between Human Activities and Ecological Conservation in the Qinghai–Xizang Plateau, China - Lingzhi Wu; Lei Zhang; Jiaming Li; Renfeng Ma (Land, 2023)
The Qinghai–Xizang Plateau is one of the important units of the major project of ecosystem protection and restoration in China’s “three zones and four belts”(2021–2035), and balancing its ecological security with rational regional development is the basis for ensuring China’s ecological stability. In this paper, the coupling mechanism between regional development intensity and ecological security is explained, and a measurement system of the relationship is designed, from which the coordination degree and type division of the coupling between regional development intensity and ecological security on the Qinghai–Xizang Plateau from 2011 to 2020 is measured. The results show the following: (1) During the study period, the regional development intensity of the Qinghai–Xizang Plateau has been increasing, with Xining and Lhasa as the “core” that drives the development and expansion of the surrounding areas. The ecological security index has been also on the rise, showing a pattern of “belt-shaped depressions in the central and western parts of the Plateau, and vertical clusters in the eastern part of the Plateau”. The depression moves toward the southern part of Xinjiang. (2) The degree of coupling and coordination between development intensity and ecological safety in each city (prefecture) on the Qinghai–Xizang Plateau has increased by different degrees, but many cities (prefectures) still show a lag in development intensity or ecological security. (3) The evolution of the pattern of coupling and coordination between regional development intensity and ecological security on the Qinghai–Xizang Plateau varies significantly, forming a pattern of “high in the east and low in the west, with multiple clusters side by side”. To some extent, this paper reveals the correlation between the spatial and temporal distributions of regional development intensity and ecological security on the Qinghai–Xizang Plateau, which can provide a basis for the regulation of human activities in the construction of ecological security barriers at the city (prefecture) level on the Qinghai–Xizang Plateau.